Poly(2-carboxyethyl acrylate-co-ethylene glycol dimethacrylate) precursor monolith. Part I. Carbodiimide assisted post-polymerization modification with octadecyl ligands for use in reversed phase capillary liquid chromatography. Issue 10 (15th June 2018) - Alharthi, Sarah; El Rassi, Ziad
Abstract: In this proof of concept study, a new precursor monolithic column was prepared by the in situ co-polymerization of 2-carboxyethyl acrylate (CEA) and ethylene glycol dimethacrylate (EDMA) in a 300 μm i.d. fused silica capillary yielding a poly(CEA- co -EDMA) monolithic column. This carboxy monolith precursor with its surface carboxyl groups was subsequently subjected to post-polymerization modification with octadecylamine (ODA) via a carbodiimide conjugation reaction. The carbodiimide with its zero-length carboxyl-to-amine coupling ability works by activating the surface carboxyl groups of the monolith for direct reaction with the primary amines of ODA via amide bond formation. This reaction, which is applied for the first time in monolithic column fabrication, yielded the octadecyl-poly(CEA- co -EDMA) monolithic capillary column for use in reversed phase capillary LC. This octadecyl column was evaluated for its RPC retention property with alkylbenzenes (ABs) and alkyl phenyl ketones (APKs). The methylene group selectivity ( α CH2 ) in the particular homologs was about the same for both ABs and APKs ( α CH2  = 1.6) using the same mobile phase composition. This may indicate that the retention mechanism is the same for both homologous series. The retention behaviors of polyaromatic hydrocarbons and chlorophenol compounds were also examined on the octadecyl capillary column. Graphical Abstract: